The synchronous improvement of strength and plasticity (SISP) in new Ni-Co based disc superalloys by controling stacking fault energy - H. Xu (Nature Portfolio, 2017)
Abstract It is a great challenge to improve the strength of disc superalloys without great loss of plasticity together since the microstructures benefiting the strength always do not avail the plasticity. Interestingly, this study shows that the trade-off relationship between strength and plasticity can be broken through decreasing stacking fault energy (SFE) in newly developed Ni-Co based disc superalloys. Axial tensile tests in the temperature range of 25 to 725 °C were carried out in these alloys with Co content ranging from 5% to 23% (wt.%). It is found that the ultimate tensile strength (UTS) and uniform elongation (UE) are improved synchronously when microtwinning is activated by decreasing the SFE at 650 and 725 °C. In contrast, only UTS is improved when stacking fault (SF) dominates the plastic deformation at 25 and 400 °C. These results may be helpful for designing advanced disc superalloys with relatively excellent strength and plasticity simultaneously.